2020
DOI: 10.3390/mti4040078
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Mixed Reality Impact on a Hand Guiding Task with a Holographic Cobot

Abstract: In the context of industrial production, a worker that wants to program a robot using the hand-guidance technique needs that the robot is available to be programmed and not in operation. This means that production with that robot is stopped during that time. A way around this constraint is to perform the same manual guidance steps on a holographic representation of the digital twin of the robot, using augmented reality technologies. However, this presents the limitation of a lack of tangibility of the visual h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Similar observations were made by Pinto et al who explored pick-andplace tasks within a mixed reality robotic teleportation environment [60]. In their implementation, the authors were looking to teach a robotic arm how to perform such tasks without using any kinematic or programming languages, but instead through human hand guidance, i.e., mimicking of user movements.…”
Section: Augmented Virtual and Mixed Realitymentioning
confidence: 72%
See 1 more Smart Citation
“…Similar observations were made by Pinto et al who explored pick-andplace tasks within a mixed reality robotic teleportation environment [60]. In their implementation, the authors were looking to teach a robotic arm how to perform such tasks without using any kinematic or programming languages, but instead through human hand guidance, i.e., mimicking of user movements.…”
Section: Augmented Virtual and Mixed Realitymentioning
confidence: 72%
“…While many of these key targets relate to the overall touchless system's performance, and therefore depend on a complex set of sub-components and their interactions, several UX studies of ultrasound mid-air haptics have reported relevant benefits thus motivating their use in touchless medical prototype systems with haptic enhanced gesture input. For example, studies have demonstrated how mid-air haptics can help localize and interact with floating widgets [49,73], enhance grasping of virtual objects in VR [61] and AR [74], improve the sense of agency [22], enhance perceived physicality of holograms [60], and improve usability and aesthetic appeal [38].…”
Section: Touchless Computer Interfaces In Hospitalsmentioning
confidence: 99%
“…Proposition 3: Digital twins are handy tools to control the robot using gestures and voice control remotely Digital Twins of human-robot systems could integrate voice and gesture control using techniques like Natural Language Processing and gesture recognition to control robots in an interactive environment remotely [42]. Similarly, DTs can allow the physical robots to be re-programed based on their imitation of a procedure demonstrated to its digital copy [49].…”
Section: Applications Scenariosmentioning
confidence: 99%
“…Garg et al [34] used another communication protocol called Socket messaging based on Client-Server architecture. Similarly, some applications use classical communication styles, such as Bluetooth [52] and wireless communication [49].…”
Section: Communication Between Dt and Ptmentioning
confidence: 99%
See 1 more Smart Citation